Mindul Leadership dalam Pencegahan Burnout Guru dan Pengembangan Budaya Kerja Sehat di Lembaga Pendidikan - Ahmad Syadidunniam; Hikmatul Hasanah; Muhammad Amar Khadafi; Muallimin Muallimin (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to analyze the role of mindful leadership in preventing teacher burnout while fostering a healthy work culture in educational institutions. The method employed is a qualitative literature review with thematic synthesis of 31 recent scholarly articles published between 2022 and 2026, focusing on mindful leadership, teacher burnout, and educational organizational culture. The analysis reveals that mindful leadership not only emphasizes leader self-awarenessbut also includes emotion regulation, empathy, and quality social interactions within educational organizations. Mindfulness-based leadership practices are effective in enhancing teachers’ self- efficacy, psychological well-being, and creating supportive work environments. Furthermore, mindful leadership contributes to developing a healthy work culture by strengthening collaboration, communication, and trust values within schools. This literature synthesis provides significant contributions for academics in under standing the interplay between mindful leadership, teacher burnout, and work culture, while offering practical guidance for school principals in designing holistic and preventive leadership strategies. The study underscores the need forfurther empirical research to examine the effectiveness of mindful leadership across diverse educational contexts.